EFEKTIVITAS GENTLE BIRTH TERHADAP PEMBERIAN ASI EKSKLUSIF - Dewi, Maria Ulfah Kurnia (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2013)
ABSTRACT: Human forming in the womb begins from infant accompanied by the right first feeding with optimum quality and quantity. The first step to realize the generation that healthy, smart, and have a good personality is by giving exclusive breastfeeding. Breastfeeding is an ideal source of nutrition with a balanced composition suitable to the needs of the baby during growth . Gentlebirth method of delivery is a quiet , gentle, polite, and take advantage of all the natural elements in the body of a human. Gentlebirth among other implemented by using Hypno-Breastfeeding and Early Initiation of Breastfeeding. Mothers who carry gentlebirth with Hypno-Breastfeeding exercises regularly and Early Initiation of Breastfeeding during labor can produce more breastmilk fluently. The purpose of this study is to determine the effectiveness of gentlebirth to exclusive breastfeeding. Analytic type is survey research with cross sectional approach. Sampling was done by purposive sampling . The sample in this study amounted to 25 people. Statistical techniques using cross tabulation and to determine the relationship variables were tested using the Contingency Coefficient . The results showed p value < Î± ( 0.05 ). Conclusions gentlebirth by method Hypno-Breastfeeding and Early Initiation of Breastfeeding effective towards exclusive breastfeeding.Keywords : exclusive breastfeeding, gentlebirth